“Koinonia” in Reformed Theology - FAZAKAS, Sándor (Studia Universitatis Babeș-Bolyai Theologia Catholica Latina, 2023)
This presentation is an edited and revised version of the presentation given at the Ecumenical International Conference “Active Participation in Community”, Pannonhalma Archabbey, 21 October 2022. The theme of the conference was synodality − accordingly, this paper aims to present the basic features of Reformed ecclesiology. It highlights the fact that adapting different forms of communion from a secular context is not a viable solution for the church, even though it remains a challenge for the church today in almost all countries. Instead, the ecclesiological and practical implications of koinonia must be considered. According to Reformed theology and Confessions of faith, the ministries, services and governance of the church derive from the koinonia with Christ and with one another. Participation in this communion requires a concrete form of ecclesial and social service; it is concretized by participation in the threefold office of Christ (royal, priestly and prophetic). Last but not least, sharing in the threefold office of Christ has an as yet unexploited ecumenical potential for the common witness of Christians.